Penggunaan Kartu RFID Dalam Sistem Presensi dan Saklar Hemat Energi Berbasis Internet of Things di Universitas Muhammadiyah Sukabumi - Kurnia, Moh Dzikri (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2024)
The implementation of Internet of Things (IoT) technology has had a significant impact on various fields, including education and the environment. This study focuses on applying Radio-Frequency Identification (RFID) technology to create an IoT-based attendance and energy-saving switch system at Muhammadiyah University of Sukabumi. The study involves students and lecturers as research subjects and uses a Prototype development method to design and implement solutions iteratively. The developed system employs RFID on Student Identity Cards (KTM) for automatic attendance recording, while an RFID-integrated energy-saving switch efficiently manages electricity consumption in the room. This research includes an analysis of the system's implementation results and Feedback from students and lecturers to assess the success and effectiveness of the developed solution. The findings indicate a significant improvement in attendance management efficiency and substantial energy savings. With this system, Muhammadiyah University of Sukabumi can optimize resource usage and create a more efficient and sustainable environment for the entire academic community.